Dispatchability of solar photovoltaics from thermochemical energy storage. (1st July 2019) - Fernández, R.; Ortiz, C.; Chacartegui, R.; Valverde, J.M.; Becerra, J.A.
Highlights: Solar photovoltaics stored by using cheap and abundant materials. The Calcium-Looping process is integrated as electricity stored system (40% efficiency) Electric-to-electric performance of the whole system reaches 57%. A notable cost reduction could be achieved as alternative to batteries. Abstract: Solar photovoltaic plants are today a competitive alternative to power plants based on fossil fuels. Cost reduction in photovoltaics modules, scalability and ease of installation of these plants are enabling a rapid worldwide expansion of the technology. Nevertheless, dispatchability still remains as the major challenge to overcome due the intrinsic variability of solar energy. Most of the current solar photovoltaic facilities at large scale lack energy storage while those with storage systems rely on expensive batteries. Batteries are based on elements such as nickel, lithium or cadmium whose scarcity hinder their sustainability for storing energy in the large scale. This manuscript presents a novel concept to integrate thermochemical energy storage in photovoltaic plants. Furthermore, the concept is also directly adaptable to wind power plants to store surplus energy. The paper analyses the suitability of the Calcium-Looping process as thermochemical energy storage system in solar photovoltaics plants. The system works as follows: part of the power produced in the solar plant provides electricity to the grid while the rest is used to supply heat for calcination of calcium carbonate. After calcination, the products of the reaction – calcium oxide and carbon dioxide- are stored separately. When power production is required, the stored products are brought together in a carbonation reactor wherein the exothermic reaction releases energy for power production. The overall system is simulated to estimate the process behaviour and results show that storage efficiencies of ∼40% can be achieved. Moreover, an economic analysis is developed to compare the proposed system with batteries. Due to the low price of natural calcium oxide precursors, such as limestone, and the expected longer lifetime of equipment as compared to batteries, the Calcium-Looping process can be considered as a potential alternative for improving dispatchability in solar photovoltaic plants.